Case studies of Global Positioning System (GPS) navigation using GPS simulator - Pang, Kuan Weng (2008)
Conduct case studies of GPS navigation using Spirent Multi-channel GPS Simulator (Model GSS6560), highlight the importance and usefulness of using a GPS simulator to achieve the test and compare with the usage of different vehicles model: static vehicle, ships, aircraft, moving vehicle.